Understanding Customer Satisfaction and Brand Equity in the E-Commerce Setting : An integration of Etail Quality Dimensions, Trust and Perceived Value - Yu, Ying Chen (2013)
The internet has become an indispensable part of modern life as it profoundly transforms the way people interact and transact with each other. With the increasing popularity of online shopping, China is one of the major online markets now and is likely to become the largest market in the future. The purpose of this study is to investigate the roles of etail quality dimensions, trust and perceived value which may influence online customer satisfaction in Chinese context. Meanwhile, it also examines the relationship between satisfaction and brand equity in the online environment. A survey method approach was adopted in this study and hypotheses are tested through multiple regression analysis from 272 usable data. The results indicate that customer satisfaction is influenced by customer service, website design, trust and perceived value. However, fulfillment is found to be insignificant to customer satisfaction, but it strongly influences perceived value, while perceived value is the major contributor to customer satisfaction. Security is positively related to trust. Customer satisfaction is found significantly influence brand equity of the online business. Drawing on the empirical findings, managerial implications and suggestions are offered.